Receita municipal: como a estrutura federativa brasileira afeta a capacidade de arrecadação e determina o grau de dependência dos municípios - Marco, Larissa Carolina de Almeida (2022)
This master's thesis aims to contribute to the debate on municipal public collection in view of our federative design. For the research, a bibliographic survey was carried out on federalism and its evolution in the organization of the Brazilian State and tax structure considering the relevant legal frameworks until 2020. For the diagnosis of revenue, the period from 2000 to 2020 was made, analyzing the Finances of Brazil database: Accounting Data of the Municipalities (SICONFI), under the responsibility of the National Treasury Secretariat (STN) of the Ministry of Economy